2021
DOI: 10.1093/ptj/pzab037
|View full text |Cite
|
Sign up to set email alerts
|

Strength, Motor Skills, and Physical Activity in Preschool-Aged Children Born Either at Less Than 30 Weeks of Gestation or at Term

Abstract: Objective Children born < 30 weeks’ gestation have more motor impairment than do children born at term (37–42 weeks’ gestation), but reported outcomes have largely focused on cerebral palsy (CP) and Developmental Coordination Disorder (DCD). The aim of this study was to compare muscle strength, motor skills and physical activity of preschool-aged children born < 30 weeks with those born at term. Methods In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…A total of 387,437 participants (49% of boys and 51% of girls) aged 3–18 years were included in this systematic review and meta-analysis, of which 11,768 were preschoolers (3–5 years; 3%), 76,928 (6–12 years; 20%) were children, and 298,741 (13–18 years; 77%) were adolescents. Twenty-six studies were conducted with preschoolers only, 8 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 13 studies with children only, 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 17 studies with adolescents only, 11 , 12 , 60 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 and 7 studies with both children and adolescents. 9 , 10 , 76 , 77 ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 387,437 participants (49% of boys and 51% of girls) aged 3–18 years were included in this systematic review and meta-analysis, of which 11,768 were preschoolers (3–5 years; 3%), 76,928 (6–12 years; 20%) were children, and 298,741 (13–18 years; 77%) were adolescents. Twenty-six studies were conducted with preschoolers only, 8 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 13 studies with children only, 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 17 studies with adolescents only, 11 , 12 , 60 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 and 7 studies with both children and adolescents. 9 , 10 , 76 , 77 ...…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the measurement of the 3 components of the 24-Hour Movement Guidelines, physical activity was obtained by device-based measures in 37 studies, 8 , 9 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 46 , 47 , 49 , 51 , 52 , 53 , 54 , 55 , 59 , 64 , 65 , 73 , 76 , 78 , 81 self-reported measures in 22 studies, 10 , 11 , 12 , 50 , 57 , 58 , 60 , 61 , 62 , 63 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 74 , 75 , 77 , 79 , 80 and parent-reported measures in 4 studies. 32 , 45 , ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though previous research has shown that physical activity and sedentary behaviour in early childhood can track over time [ 37 , 38 ], minimal evidence exists on whether 24-Hour Movement Guideline adherence tracks over time. In the meta-analysis previously discussed, only eight out of 63 included studies were longitudinal, including three in the preschool-aged group [ 10 12 ]. Of these eight studies, only two examined the tracking of guideline adherence [ 22 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The adverse pregnancy outcomes (APOs) that we will focus on in this work -including early gestational age (GA) at delivery (a continuous surrogate for preterm birth), gestational diabetes, severe preeclampsia (severe pree), or preeclampsia superimposed on hypertension (superimposed pree) -are associated with severe short-and long-term consequences for both the mother and infant (1)(2)(3)(4), underscoring the importance of management and prevention (5)(6)(7)(8)(9). Currently, however, highly efficacious therapeutic options to prevent APOs are lacking, highlighting the critical clinical need to identify actionable risk targets and prevent their development (10).…”
Section: Introductionmentioning
confidence: 99%